1999
DOI: 10.1103/physreva.60.r761
|View full text |Cite
|
Sign up to set email alerts
|

Large numbers of cold metastable helium atoms in a magneto-optical trap

Abstract: We report loading of 1.5ϫ10 9 metastable triplet helium atoms in a large magneto-optical trap, using far-red-detuned laser beams. We fully characterized this trap by measuring trap losses and absorption of a probe beam. From the highly nonexponential trap decay we derive Penning ionization loss rate coefficients for two detunings: 5.3(9)ϫ10 Ϫ9 cm 3 /s at Ϫ35 MHz and 3.7(6)ϫ10 Ϫ9 cm 3 /s at Ϫ44 MHz. Also, we find that the loss rate is maximum at Ϫ5 MHz detuning, where the rate is 1.3(3)ϫ10 Ϫ8 cm 3 /s, much larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 16 publications
6
67
3
Order By: Relevance
“…For metastable atoms in a MOT, light assisted collisions between the trapped atoms can have large rate constants and the two-body losses are often dominant. This phenomenon has been observed in every metastable noble gas MOT equipped with an ion detector (Bardou et al, 1992;Kumakura and Morita, 1999;Kunugita et al, 1997;Mastwijk et al, 1998;Rooijakkers et al, 1997b;Shimizu et al, 1989;Spoden et al, 2005;Tol et al, 1999;Walhout et al, 1994). The experiment of Bardou et al, demonstrated that the ion rate could be a probe of the local density of atoms.…”
Section: Detection By Use Of Penning Ionizationmentioning
confidence: 95%
See 3 more Smart Citations
“…For metastable atoms in a MOT, light assisted collisions between the trapped atoms can have large rate constants and the two-body losses are often dominant. This phenomenon has been observed in every metastable noble gas MOT equipped with an ion detector (Bardou et al, 1992;Kumakura and Morita, 1999;Kunugita et al, 1997;Mastwijk et al, 1998;Rooijakkers et al, 1997b;Shimizu et al, 1989;Spoden et al, 2005;Tol et al, 1999;Walhout et al, 1994). The experiment of Bardou et al, demonstrated that the ion rate could be a probe of the local density of atoms.…”
Section: Detection By Use Of Penning Ionizationmentioning
confidence: 95%
“…2 because β = 2K. For He* samples in a 1083 nm MOT Kumakura and Morita, 1999;McNamara et al, 2007;Pereira Dos Santos et al, 2001b;Stas et al, 2004Stas et al, , 2006Tol et al, 1999) or 389 nm MOT (Koelemeij et al, 2003Tychkov et al, 2004), collisional loss mechanisms give rise to significant trap loss. Quadratic trap loss is determined by collisions between trapped He* atoms, while linear trap loss results from collisions with background gas particles.…”
Section: Measurement Of Ionizing Collisions In a Motmentioning
confidence: 99%
See 2 more Smart Citations
“…This has provided a unique setting for the study of cold ionizing collisions in which the highly efficient, direct detection of collisional loss products using charged-particle detectors is possible. In the past, several experiments have made use of microchannel plate (MCP) detectors to measure ion production rates and investigate collisional losses in 3 He* [20] and 4 He* [20,21,22,23]. Having realized the ability to trap large numbers (>10 8 ) of both isotopes (either individually or simultaneously) [19], we have previously reported on the isotopic differences between binary homonuclear collisions of 3 He and 4 He [13] in the absence of resonant light, resolving inconsistencies in prior experimental and theoretical results.…”
Section: Introductionmentioning
confidence: 99%